Surface-observation-constrained high-frequency coal mine methane emissions in Shanxi, China, reveal more emissions than inventories, consistent with satellite inversion - F. Lu; K. Qin; J. B. Cohen; Q. He; P. Tiwari; W. Hu; C. Ye; Y. Shan; Q. Xu; S. Wang; Q. Tu (Atmospheric Chemistry and Physics)
This work focuses on Changzhi, Shanxi, China, a city and surrounding rural region with one of the highest atmospheric concentrations of methane (CH4) worldwide (campaign-wide minimum, mean, standard deviation, and max observations: 2.0, 2.9, 1.3, and 16 ppm) due to a rapid increase in the mining, production, and use of coal over the past decade. An intensive 15 d surface observation campaign of CH4 concentration is used to drive a new analytical, mass-conserving method to compute and attribute CH4 emissions. Observations made in concentric circles at 1, 3, and 5 km around a high-production high gas coal mine yielded emissions of 0.73, 0.28, and 0.15 ppm min−1, respectively. For attribution a two-box mass-conserving model was used to identify the known mine's emissions from 0.042–5.3 ppm min−1 and a previously unidentified mine's emission from 0.22–7.9 ppm min−1. These results demonstrate the importance of simultaneously quantifying both the spatial and temporal distribution of CH4 emissions to better control regional-scale CH4 emissions. Results of the attribution are used in tandem with observations of boundary layer height to quantify policy-relevant emissions from the two coal mines as 6860 ± 3520 and 1010 ± 347 kg h−1, respectively. Both mines display a fat-tailed distribution, with respective 25th percentile, median, and 75th percentile values of [1600, 3070, 10 500] and [755, 1090, 1420] kg h−1. These findings are demonstrated to be higher than CH4 emissions from equivalent oil and gas operations in the USA, with one about double and the other similar to day-to-day emissions inverted over 5 years using TROPOMI over the same region.